Uji Karakteristik Biokimia Kandungan Protein Total Ampas Organik Ecoenzyme - Nada Wafiq Hijriah (Journal of Biotropical Research and Nature Technology, 2024)
Organic waste can be utilized to become ecoenyme. Ecoenzyme is the result of organic waste baskets such as kitchen waste which are not valuable into environmentally friendly enzymes that are very useful. Ecoenzyme is a complex solution produced by a basket of fresh organic waste (fresh fruits and vegetables), brown sugar or molasses and water. Ecoenzymes are organic compounds. The liquid produced by heating ecoenzyme can be used as a disinfectant and hand sanitizer, in the health sector ecoenzyme can be used as an infection and allergy reliever in children and to heal wounds. Apart from the liquid which has many benefits, the dregs resulting from cooling ecoenzyme can also be used in agriculture as organic fertilizer. At this time the agricultural sector still uses a lot of inorganic fertilizers (chemical fertilizers), excessive application of inorganic fertilizers can cause physical, chemical and biological damage to the soil. Will have an impact on plant metabolism. The use of ecoenzyme waste can be an environmentally friendly fertilizer solution. The research method used was descriptive research with the aim of obtaining total protein content from ecoenzyme waste. The method used is the Warburgh Christian method. The result of measuring the total protein content of dry ecoenzyme dregs was 0.050 mg/ml. Protein contains amino acids that can be used for plant growth (structural function) and enzymes (metabolic function). This amino acid can increase the amount of chlorophyll in plants, increase photosynthetic activity, and promote root growth. Amino acids can also regulate stomata optimally by controlling plant transpiration and increasing the reduction of carbon dioxide which will be converted into carbohydrates.